Effects of metal ions on the flotation separation of spodumene from feldspar and quartz - Xie, Ruiqi; Zhu, Yimin; Liu, Jie; Li, Yanjun (Minerals engineering, 2021)
•Effects of Ca(II), Mg(II), Cu(II), and Fe(III) on the flotation separation of spodumene from feldspar and quartz were investigated.•Ca(II), Mg(II), and Cu(II) selectively improved the flotation of spodumene, whereas Fe(III) showed strong activation ability but low selectivity toward spodumene.•At a pH of approximately 7, Ca(II) and Mg(II) preferentially reacted with spodumene, facilitating the separation of spodumene.•At a pH of approximately 7, some Fe(III) and Cu(II) species preferably reacted with feldspar and quartz, impairing the separation of spodumene. The effects of Ca(II), Mg(II), Cu(II), and Fe(III) on the flotation separation of spodumene from feldspar and quartz were investigated by single-mineral and artificial-mixed-ore flotation experiments using α-bromododecanoic acid (α-BDDA) as a collector. At pH≈7, Ca(II), Mg(II), and Cu(II) selectively improved the flotation of spodumene, which facilitated the separation of spodumene. Although Fe(III) exhibited strong activation ability, its selectivity toward spodumene was low, which impaired the separation of spodumene. Moreover, the sequence of addition of metal ions had an impact on the separation of spodumene. When Ca(II) and Mg(II) were used as activators in the artificial-mixed-ore flotation experiments, concentrates with recoveries of 75.6% and 76.3% and Li2O grades of 5.8% and 5.2% were obtained, respectively. Adsorption and activation mechanisms of metal ions were analyzed by adsorption amount measurements, Fourier transform infrared spectroscopy, species distribution calculation, and frontier orbital theory calculation. Results indicated that the amount of α-BDDA adsorbed on spodumene was higher than those adsorbed on feldspar and quartz when Ca(II), Mg(II), and Cu(II) were employed as activators, which led to a higher recovery of spodumene. When the pH was approximately 7, Ca(II), Mg(II), Fe(III), and Cu(II) were mainly present as Ca2+, Mg2+, Fe(OH)3 and Fe(OH)2+, and Cu(OH)2, Cu2+, and Cu(OH)+, respectively. The results of frontier orbital theory calculations demonstrated that α-BBBA, Ca2+, and Mg2+ easily adsorbed on spodumene than on feldspar and quartz. Therefore, Ca(II) and Mg(II) facilitated the separation of spodumene. However, Fe(OH)2+ preferentially reacted with spodumene, whereas Fe(OH)3 preferably reacted with feldspar and quartz, which caused low selectivity of Fe(III) toward spodumene. Similarly, Cu2+ and Cu(OH)+ easily adsorbed on spodumene, whereas Cu(OH)2 preferentially adsorbed on feldspar and quartz. Thus, the selectivity of Cu(II) toward spodumene was inferior compared to those of Ca(II) and Mg(II).